Optical coherence tomography angiography showing perifoveal capillary stability 30 years after fluorescein angiography - Nikisha Kothari; Nidhi Relhan; Harry W. Flynn, Jr. (American Journal of Ophthalmology Case Reports, 2018)
Purpose: To report the Optical Coherence Tomography Angiography (OCTA) results as a novel non-invasive diagnostic modality which provides useful information regarding the status of blood flow in diabetic retinopathy. The current study is a long-term follow-up of eyes of patients with proliferative diabetic retinopathy managed with panretinal photocoagulation. Observations: Two patients with proliferative diabetic retinopathy (PDR) were treated with panretinal photocoagulation (PRP) in both eyes in the early 1980s. Fluorescein angiography performed at the baseline visit and follow-up Optical Coherence Tomography Angiography performed at 30 years after initial PRP treatment showed remarkable stability of the perifoveal capillary network. Visual acuity initially and at last follow-up remained 20/25 or better in these patients. Conclusions and importance: Fluorescein angiography and Optical Coherence Tomography Angiography demonstrated that the integrity of the perifoveal capillary network remained remarkably stable at 30 years. Similarly, the visual outcomes were stable inspite of advanced PDR at baseline.